Factores que afectan la construcción de alcantarillado sanitario para la Constructora Fernández Vaglio S.A. - Coto-Chinchilla, Luis Roberto (Instituto Tecnológico de Costa Rica, 2018)
The work presented below is based on the determination of factors that affect the construction of a sanitary pipeline project, to propose tools and methods to be able to reduce the elements identified to the maximum. To locate the factors to be corrected, a control sheet was implemented, which was filled daily by the construction masters and in this way the affectations that occurred were recorded. Once the most frequent factors are known, proposals for improvement are made under the Lean Construction philosophy, which seeks to work more efficiently and use only the resources that are completely necessary. The data shows that there are activities that are not being worked in the right way, which is why they are generating cost overruns and arrears. In addition, with the review of the schedule and the cash flows it is visualized as there is a delay in production, so corrective measures must be taken. At the end of the project, it is determined that to improve the processes there must be field inspection by the project engineers to know if the work is being carried out properly. Also, that a planning that integrates all the work team is a useful methodology for the development of projects
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Factores; Construcción; Control; Procesos; Métodos; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering